Implementation Of Law Number 11 Of 2020 Concerning Employment Creating In The Making Of Collective Labor Agreements (PKB) - Sugeng Prayitno; Aji Aji (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Abstract In Industrial Relations, disputes often occur between workers and employers, which can be caused due to incompatibility regarding the manufacture, and/or changes to the working conditions applied in work agreements, or company regulations or collective bargaining agreements, or a lack of ability to understand a statutory regulation. Based on this, the author is interested in conducting research on the Implementation of Law Number 11 of 2020 Concerning Job Creation in Making Collective Labor Agreements (PKB). In this study the authors conducted research using normative legal research methods or legal research literature research which mainly used literature or secondary data. The type of data used in this study was secondary data, namely by using primary legal materials and secondary legal materials collected. through library research. In fact, the Collective Labor Agreement is a means for the parties (companies and workers) in building industrial relations, so that problems that occur within the scope of employment can be minimized and can be anticipated.